High-alkaline water-splitting activity of mesoporous 3D heterostructures: an amorphous-shell@crystalline-core nano-assembly of Co-Ni-phosphate ultrathin-nanosheets and V- doped cobalt-nitride nanowires - Singh, Thangjam Ibomcha; Maibam, Ashakiran; Cha, Dun Chan; Yoo, Sunghoon; BabaRao, Ravichandar; Lee, Sang Uck; Lee, Seunghyun (Advanced Science, 2022)
Introducing amorphous and ultrathin nanosheets of transition bimetal phosphate arrays that are highly active in the oxygen evolution reaction (OER) as shells over an electronically modulated crystalline core with low hydrogen absorption energy for an excellent hydrogen evolution reaction (HER) can boost the sluggish kinetics of the OER and HER in alkaline electrolytes. Therefore, in this study, ultrathin and amorphous cobalt-nickel-phosphate (CoNiPOx) nanosheet arrays are deposited over vanadium (V)-doped cobalt-nitride (V-3%-Co4N) crystalline core nanowires to obtain amorphous-shell@crystalline-core mesoporous 3D-heterostructures (CoNiPOx@V-Co4N/NF) as bifunctional electrocatalysts. The optimized electrocatalyst shows extremely low HER and OER overpotentials of 53 and 270 mV at 10 mA cm(-2), respectively. The CoNiPOx@V-3%-Co4N/NF (+/-) electrolyzer utilizing the electrocatalyst as both anode and cathode demonstrates remarkable overall water-splitting activity, requiring a cell potential of only 1.52 V at 10 mA cm(-2), 30 mV lower than that of the RuO2/NF (+)/20%-Pt/C/NF (-) electrolyzer. Such impressive bifunctional activities can be attributed to abundant active sites, adjusted electronic structure, lower charge-transfer resistance, enhanced electrochemically active surface area (ECSA), and surface- and volume-confined electrocatalysis resulting from the synergistic effects of the crystalline V-3%-Co4N core and amorphous CoNiPOx shells boosting water splitting in alkaline media.
Keywords: core-shell; hydrogen productions; metal nitrides; metal phosphates; synergistic effect; water-splitting

Heterogeneous acid-base organocatalyst for cascade deacetalisation-knoevenagel condensations - Chhetri, Ashis; Maibam, Ashakiran; Maniam, Subashani; BabaRao, Ravichandar; Wilson, Karen; Lee, Adam F.; Mitra, Joyee (ChemSusChem, 2024)
Multifunctional heterogeneous catalysts are an effective strategy to drive chemical cascades, with attendant time, resource and cost efficiencies by eliminating unit operations arising in normal multistep processes. Despite advances in the design of such catalysts, the fabrication of proximate, chemically antagonistic active sites remains a challenge for inorganic materials science. Hydrogen-bonded organocatalysts offer new opportunities for the molecular level design of multifunctional structures capable of stabilising antagonistic active sites. We report the catalytic application of a charge-assisted, hydrogen-bonded crystalline material, bis(melaminium)adipate (BMA), synthesised from melamine and adipic acid, which possesses proximate acid-base sites. BMA exhibits high activity for the cascade deacetalisation-Knoevenagel condensation of dimethyl acetals to form benzylidenemalononitriles under mild conditions in water; BMA is amenable to large-scale manufacture and recycling with minimal deactivation. Computational modelling of the melaminium cation in protonated BMA explains the observed catalytic reactivity, and identifies the first demethoxylation step as rate-limiting, which is in good agreement with time-dependent 1H NMR and kinetic experiments. A broad substrate scope for the cascade transformation of aromatic dimethyl acetals is demonstrated.
Keywords: Antagonistic acid-base sites; Charge-assisted hydrogen bonding; Chemical cascade; organocatalysis; Sustainable catalysis